Influence of genetic polymorphisms in DICER and XPO5 genes on the risk of coronary artery disease and circulating levels of vascular miRNAs. Issue 180 (August 2019) - Borghini, Andrea; Pulignani, Silvia; Mercuri, Antonella; Vecoli, Cecilia; Turchi, Stefano; Carpeggiani, Clara; Andreassi, Maria Grazia
Abstract: Introduction: Single-nucleotide polymorphisms (SNPs) in microRNA (miRNA) machinery genes may affect the regulatory capacity of miRNAs by impacting their biogenesis. The aim of the study was to analyze the association between SNPs in two key genes ( DICER rs1057035T>C and XPO5 rs11077A>C ) and coronary artery disease (CAD) risk as well as to examine their effects on circulating levels of vascular miRNAs. Materials and methods: Within the Italian GENOCOR cohort, we studied a cohort of 557 patients (502 males, 57 ± 9 years) with angiographically documented CAD. A total of 443 healthy controls (262 males, 56 ± 12 years) was also enrolled. Genotyping was determined by using a TaqMan®SNP genotyping assay. Analysis of miR-132 and miR-140-3p was assessed in a subset of 70 CAD patients by using qRT-PCR. Results: There were statistically significant differences between CAD patients and healthy controls in the distribution of both DICER and XPO5 genotypes (p = 0.03 and p = 0.02, respectively). Multivariate analysis showed a significantly decreased risk of CAD by 50% in patients with DICER rs105703CC genotype as compared to TC heterozygote and TT homozygote patients (ORadjusted  = 0.50; CI: 0.30–0.83, p = 0.007). In a recessive model, the XPO5 rs11077 CC genotype was associated with a 32% reduced risk of CAD (ORadjusted  = 0.68; CI: 0.30–0.99 p = 0.047). XPO5 rs11077 CC genotype was significantly associated with higher levels of both miRNA-132 (p = 0.04) and miRNA-140-3p (p = 0.03). Conclusions: Genetic polymorphisms in DICER and XPO5 genes are associated with a decreased risk of CAD, probably by impacting expression levels of vascular and cardiac-specific miRNAs. Further studies are needed to better elucidate the biological relevance of both variants in CAD development. Highlights: SNPs in miRNA biogenesis pathway may impact the miRNA activity and affect CAD risk. DICER rs1057035 T>C and XPO5 rs11077 A>C are associated with a decreased CAD risk. The levels of two vascular miRNAs (miRNA-132 and miRNA-140-3p) vary by genotypes.